An isosteric triaza analogue of a polycyclic aromatic hydrocarbon monkey saddle - Kirschbaum, Tobias; Rominger, Frank; Mastalerz, Michael (Chemistry - a European journal, 2020)
Since a few years, the interest in negatively-curved fused polycyclic aromatic hydrocarbons (PAHs) has significantly increased. Recently, the first chiral negatively-curved PAH with the topology of a monkey saddle was introduced. Herein the synthesis of its triaza congener is reported. The influence of this CH↔N exchange on photophysical and electrochemical properties is studied as well as the isomerization process of the enantiomers. The aza analogue has a significantly higher inversion barrier, which makes it easier to handle at room temperature. All experimental results are underpinned by theoretical DFT calculations.
First published: 15 June 2020
Gesehen am 03.11.2021